(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
Prior to the Second World War Europeâ€™s ruling classes had no perception of the destiny of the modern city. This despite the fact that almost a century earlier Baudelaire had intoned the decadence of their most beautiful city. Proud of their ordered, authoritative, and often authoritarian capitals, Europeans saw history as a course predestined to create that miracle of civilisation exemplified by the metropolis of the old continent: wealthy, with a rigid social hierarchy, symbolically, physically and culturally rooted in history, firmly established at the summit of a providential, though still highly dramatic process. The metropolises of Europe were perceived, in the end, as organisms at the pinnacle of their conscious maturity and the height of their industrial and financial might. They appeared to posses an ability to self-regulate internal and external conflicts, imposing models of assimilation and reciprocal adaptation upon sources of imbalances, conceived by imagining the possible effects of disturbances and anticipating their transformations â€“ thus adopting planning in the form of a series of direct systematic operations. Two years later, in 1939, Claude LÃ©vi Strauss went much further; his direct experience with SÃ£o Paulo, Brazil (and New York) convinced him that the modern metropolis, which he observed and which observed him with a thousand hidden eyes as he, a foreigner, crossed it, cannot be judged according to the parameters of architecture (thus also excluding those of planning), but with those of the landscape; and to the same degree that everything in the natural landscape is in transformation, simultaneously luxuriance and putrefaction, he claimed that Â«the cities of the New World [â€¦] pass from first youth to decrepitude with no intermediary stageÂ». With no intermediate stage: this is the most important clue, the tag that for the great anthropologist implicitly, though peremptorily, invalidated the idea that the cities of the New World are truly part of history. LÃ©vi Strauss, who certainly learned to be a narrator of cultures and ethnographic contexts as Walter Benjamin learned to be a narrator of cities, froze â€“ despite being captivated â€“ in front of the metropolises of the New World, home to a coexistence between past and present, and between proximity and distance. Perhaps the time has come to truly study the worldâ€™s metropolises as individuals in the midst â€“ or at the beginning â€“ of their evolutionary age seeking to establish their stage of development and that of their parts, in the concreteness of reality. The term stage is used here to refer to a recognisable and well-characterised structure that is organised and relatively balanced â€“ equivalent to one of the stages of Jean Piagetâ€™s theory of development. This would make it possible in the most appropriate terms to solicit different urban communities to autonomously imagine the effects of on-going disturbances, accompanying them as they realistically express their fears and desires and anticipate the form and objectives of tangible operations to be implemented within the limits of a communityâ€™s available resources and level of organisation and the pedagogic capacities of the city and its government. Â Â Â